Stability of hybrid composite rod to high temperatures - Yu. V. Nemirovskiy; D. V. Mokhovnev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The problem of stability of a rod made of two materials under temperature and force loading beyond the limits of elasticity is posed. The deformation law of materials is approximated by a cubic polynomial over the entire deformation diagram, which greatly simplifies the formulation of the stability problem. The influence of temperature on the deformation law is taken into account. The process of loss of stability is considered in the framework of the concept of continuous loading by F. R. Shanley. The stability problem is reduced to solving a linear homogeneous differential equation with linear homogeneous boundary conditions. Examples of the calculation of the critical parameters of thermal and force loading are given